ENVIRONMENTAL UNCERTAINTY IN MODERATING BUDGETARY PARTICIPATION AND ORGANIZATIONAL COMMITMENT TO BUDGETARY SLACK - putu kepramareni; Ida Ayu Nyoman Yuliastuti; Gusti Ayu Ari Dewi (Universitas Mercu Buana, 2020)
Budgetary slack is done to facilitate the achievement of the budget by budgeting low income and high budgeting. This study aims to determine the effect of budgetary participation and organizational commitment on budgetary slack with environmental uncertainty as a moderating variable. The population used in this study was 19 Starred Hotels in Ubud Gianyar with a total of 2,151 employees. The method of determining the sample using a purposive sampling technique, so that the sample used is as many as 152 employees found in 19 Starred Hotels in Ubud, Gianyar. Data collection was carried out using a questionnaire. The analysis technique used is MRA (Moderated Regression Analysis). The results showed that budgetary participation had a positive effect on budgetary slack, while organizational commitment had a negative effect on budgetary slack. Environmental uncertainty can strengthen the influence of budgetary participation on budgetary slack, and environmental uncertainty can weaken the influence of organizational commitment on budgetary slack.